2014
DOI: 10.1371/journal.pone.0089483
|View full text |Cite
|
Sign up to set email alerts
|

The Pentachlorophenol Metabolite Tetrachlorohydroquinone Induces Massive ROS and Prolonged p-ERK Expression in Splenocytes, Leading to Inhibition of Apoptosis and Necrotic Cell Death

Abstract: Pentachlorophenol (PCP) has been used extensively as a biocide and a wood preservative and has been reported to be immunosuppressive in rodents and humans. Tetrachlorohydroquinone (TCHQ) is a major metabolite of PCP. TCHQ has been identified as the main cause of PCP-induced genotoxicity due to reactive oxidant stress (ROS). However, the precise mechanisms associated with the immunotoxic effects of PCP and TCHQ remain unclear. The aim of this study was to examine the effects of PCP and TCHQ on the induction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 89 publications
(88 reference statements)
3
15
0
Order By: Relevance
“…Arrest of cell cycling is usually observed in stressed cells, and it can result in apoptosis, necrosis, or both mechanisms simultaneously . It was reported that different types of ERK activation could lead to distinct cell death mechanisms, that is, apoptosis or necrosis . In this study, the expression of p‐ERK after exposure decreased in a time‐ and concentration‐dependent manner, indicating the presence of cell cycle arrest (Fig.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Arrest of cell cycling is usually observed in stressed cells, and it can result in apoptosis, necrosis, or both mechanisms simultaneously . It was reported that different types of ERK activation could lead to distinct cell death mechanisms, that is, apoptosis or necrosis . In this study, the expression of p‐ERK after exposure decreased in a time‐ and concentration‐dependent manner, indicating the presence of cell cycle arrest (Fig.…”
Section: Discussionsupporting
confidence: 49%
“…50 It was reported that different types of ERK activation could lead to distinct cell death mechanisms, that is, apoptosis or necrosis. 51 In this study, the expression of p-ERK after exposure decreased in a time-and concentration-dependent manner, indicating the presence of cell cycle arrest (Fig. 9).…”
supporting
confidence: 56%
“…Moreover, pretreatment with TCDD resulted in a time-dependent down-regulation of Bad and up-regulation of Bcl-xl and Bcl-2 after STS treatment ( Figure 3C ). Previous studies indicated loss of mitochondria membrane integrity is one of the early events leading to apoptosis [28] . To evaluate the effects of TCDD on preventing mitochondria membrane potential loss in response to STS, cells were pretreated with the fluorescent mitochondria staining dye DiOC 6 , and the changes of mitochondrial membrane potential were measured by flow cytometry.…”
Section: Resultsmentioning
confidence: 99%
“…Membrane potential can be detected by incubation of cells with DiOC 6 . The interaction of mitochondria with DiOC6 is dependent on the stability of transmembrane potential and its uptake is reduced in apoptotic cells [28] . Therefore, apoptotic cells, with decreased mitochondrial membrane potential, showed reduced DiOC 6 fluorescence.…”
Section: Methodsmentioning
confidence: 99%
“…Exposure of HepG2 cells to 10 µM TCHQ produces significant amounts of reactive oxygen species (ROS) and decreases mitochondrial membrane potential ( 46 ). Exposure of primary splenocytes to 12.5 µM TCHQ produces ROS and substantially decreases viability ( 47 ). Treatment of hamster lung fibroblasts with 25 µM TCHQ for 1 h increases the level of 8-hydroxy-2-oxoguanosine, a marker of oxidative DNA damage, and induces single-strand breaks ( 48 ).…”
Section: Introductionmentioning
confidence: 99%